Evaluation of the effect of post‐translational modification toward protein structure: Chemical synthesis of glycosyl crambins having either a high mannose‐type or a complex‐type oligosaccharide. Issue 4 (4th November 2016) - Dedola, Simone; Izumi, Masayuki; Makimura, Yutaka; Ito, Yukishige; Kajihara, Yasuhiro
ABSTRACT: Glycoproteins are assembled and folded in the endoplasmic reticulum (ER) and transported to the Golgi for further processing of their oligosaccharides. During these processes, two types of oligosaccharides are used: that is, high mannose‐type oligosaccharide in the ER and complex‐type oligosaccharide in the Golgi. We were interested to know how two different types of oligosaccharides could influence the folding pathway or the final three‐dimensional structure of the glycoproteins. For this purpose, we synthesized a new glycosyl crambin having complex‐type oligosaccharide and evaluated the folding process, the final protein structure analyzed by NMR, and compared the CD spectra with previously synthesized glycosyl crambin bearing high mannose‐type oligosaccharides. From our analysis, we found that the two different oligosaccharides do not influence the folding pathway in vitro and the final structure of the small glycoproteins. © 2015 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 106: 446–452, 2016.